Application of optimized lubri-cooling technique in through-feed centerless grinding process of bearing steel SAE 52100 - Neto, Luiz Maurício Gonçalves; Rodriguez, Rafael Lemes [UNESP]; Lopes, José Claudio [UNESP]; Ribeiro, Fernando Sabino Fonteque [UNESP]; Królczyk, Grzegorz M.; de Ângelo Sanchez, Luiz Eduardo [UNESP]; de Mello, Hamilton José [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer Nature, 2022)
Through-feed centerless grinding is a high-productivity machining process widely used for mass production of cylindrical parts and rotationally symmetrical parts in automotive and bearing industries. Grinding process is strictly related to large amount of heat generated in the cutting zone, i.e., the interface between the workpiece and the abrasive tool. This process characteristic makes pivotal and indispensable the effects of lubrication and cooling provided by metal working fluid (MWF) in order to avoid thermal damage to the part during grinding. In this regard, this work aims to contribute to the study and application of cutting fluid in the process of this grinding process, comparing the effects in terms of workpiece integrity between the conventional technique and the optimized technique developed for the rational use of cutting fluids by the application of a novel multitubular nozzle. The multitubular nozzle was employed with emulsion (ME) and emulsion and compressed air simultaneously (ME + CA). Both techniques were compared to conventional nozzle (CN) application. All techniques were tested for four different flow rates: 10, 20, 30, and 40 L/min. Surface roughness of the ground surface, roundness deviation, and residual stress were analyzed. Additionally, optical microscopy images of grinding wheel cutting surface and SEM images for each condition surface were recorded. Regarding the three techniques of cutting fluid application (CN, ME, and ME + CA) in the process of through-feed centerless grinding, in general, a better performance was recorded for application of the new concept of developed multi-tube nozzle. The best grinding conditions were observed using ME + CA and ME for the flow rate of 40 L/min.
Keywords: Compressed air; Cutting fluid; Multitubular nozzle; Through-feed centerless grinding